Self-perceived uselessness and associated factors among older adults in China - Zhao, Yuan (BMC Geriatr, 2017)
BACKGROUND: Self-perceived uselessness is associated with poor health and high mortality among older adults in China. However, it is unclear which demographic, psychosocial, behavioral and health factors are associated with self-perceived uselessness. METHODS: Data came from four waves (2005, 2008, 2011 and 2014) of the largest nationwide longitudinal survey of the population aged 65 and older in China (26,624 individuals contributed 48,476 observations). This study aimed to systematically investigate factors associated with self-perceived uselessness based on the proposed REHAB framework that includes resources (R), environments (E), health (H), fixed attributes (A) and behaviors (B). Self-perceived uselessness was measured by a single item: “with age, do you feel more useless?” and coded by frequency: high (always and often), moderate (sometimes) and low (seldom and never). Multinomial logistic regression models with low frequency as the reference category were employed to identify REHAB risk factors associated with self-perceived uselessness. RESULTS: Most factors in the REHAB framework were associated with self-perceived uselessness, although some social environmental factors in the full model were not significant. Specifically, more socioeconomic resources were associated with reduced relative risk ratio (RRR) of high or moderate frequency of self-perceived uselessness relative to low frequency. More environmental family/social support was associated with lower RRR of high frequency of self-perceived uselessness. Cultural factors such as coresidence with children and intergenerational transfer were associated with reduced RRR of high frequency of self-perceived uselessness. Indicators of poor health status such as disability and loneliness were associated with greater RRR of high or moderate frequency of self-perceived uselessness. Fixed attributes of older age and Han ethnicity were associated with increased RRR of high frequency of self-perceived uselessness; whereas optimism and self-control were associated with reduced RRR. Behaviors including regular consumption of alcohol, regular exercise, social participation and leisure activities were associated with reduced RRR of high frequency of self-perceived uselessness. CONCLUSIONS: Self-perceived uselessness was associated with a wide range of factors in the REHAB framework. The findings could have important implications for China to develop and target community health programs to improve self-perceived usefulness among older adults.